SUICIDAL IDEATION AND ASSOCIATED FACTORS AMONG HEALTH SCIENCES STUDENTS IN THE PANDEMIC TIMES - Silva, Bruno de Andrade; Menezes, Andreia Freire de; Abud, Ana Cristina Freire; Freitas, Carla Kalline Alves Cartaxo; Gois, Cristiane Franca Lisboa; Diniz, Fernanda Santos; Almeida Junior, Enoque Chaves de (Cogitare Enfermagem, 2024)
Objective: To verify the existence of an association between suicidal ideation, social support, and anxious-depressive symptoms among Health Sciences students. Method: Quantitative, cross-sectional study. Data collection took place from November 2020 to July 2021 in Sergipe - Brazil, using the Sociodemographic Questionnaire, Suicidal Ideation Questionnaire, Satisfaction with Social Support Scale, and Anxiety, Depression, and Stress Scale. Simple and multiple linear regression coefficients and odds ratios were estimated. Results: Of the 190 interviewees, 57 (30%) had low satisfaction with social support, 66 (34.8%) reported symptoms of severe or very severe depression, 32 (16.8%) had a potential risk of suicide, which can be increased by 18% in people with depression. Conclusion: Stress, anxiety, and depression are risk factors for suicidal ideation in health students. Social support becomes an ally in emotional control, in the reduction of psychological suffering, and in the precipitation of mental disorders in students.